Analysis of the Peculiarities of Pedestrian Traffic in the Historical European Part of the City (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
The article considers the problems of pedestrian traffic in the central historical parts of the cities of Uzbekistan and the development of the street and road network. The historical European part of the city of Samarkand is taken as an example and proposals for the organization of pedestrian streets and sidewalks are made.